The Effect of Using Spelling Bee Game on Student’s Reading Comprehension of The Eighth-Grade at SMPN 7 Medan - Angelica Alexia Navaratna; Maria Megantri Hutasoit; Ester Enjelina Simanjuntak; Natalia Widya Pasca Tarigan (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research aims to determine wheater employing the language game Spelling Bee as a reading comprehension strategy for eighth-graders at SMPN 7 Medan in the academic year 2021/2022 is effective or not. This quantitative research with a quasi-experimental study utilizes a pretest, treatment, and post-test design. The population of this study is 288 eighth-grade students at SMPN 7 Medan in the academic year 2021/2022, and the sample is 40 students. The data is collected through a multiple-choice test consisting of 10 questions with four choices and the write-down of the meanings of 10 words. The Spelling Bee game contains the study's independent variable, while students' reading comprehension is the study's dependent variable. According to the computation, the post-test result shows that the experimental group's mean score is 85, which is considered good, and the control group's mean is 58,75, which is considered sufficient. It can be concluded that using the language game Spelling Bee as a strategy effectively improves students' reading comprehension at SMPN 7 Medan eighth-grade students in the academic year 2021/2022.